Penerapan Filsafat Progresivisme dalam Pembelajaran Berdiferensiasi Pada Materi Aritmatika Sosial Siswa Kelas VII - Nana Puspita (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
This research aims to determine the differentiated learning process in social arithmetic material for class VII students regarding the philosophy of the progressivism school of education at SMPN 1 Bandar Dua which was carried out in the second semester of the 2022/2023 academic year. This research method is pure experiment (true experiment design). Quantitative descriptive approach with a pretest-posttest control design research design. Data analysis techniques using pretest posttest score scoring, response questionnaire scoring, gain score and normality test. The research results showed that before treatment the pre-test score in the experimental class with a sample of 32 people had an average score of 68, standard deviation 5.5. Meanwhile, the results after the posttest were carried out in the experimental class had an average score of 85 with a standard deviation of 4.7. Meanwhile, in the control class before treatment, the pretest score in the control class with a sample of 32 people had an average score of 61, standard deviation 7.9. For the gain score normality test, the experimental class and control class each have a medium classification interpretation. Meanwhile, the test results show that T count > T table at the 5% level (9.5 > 4.0), which means that it can be concluded that the learning process is significantly differentiated due to progressivism. The progressivism is seen in the student center so that there is progress with the supporting capacity of differentiation of content, processes and products so that students are more creative.